2010
DOI: 10.1007/s10919-010-0089-7
|View full text |Cite
|
Sign up to set email alerts
|

The Semantic Specificity Hypothesis: When Gestures Do Not Depend Upon the Presence of a Listener

Abstract: Humans gesture even when their gestures can serve no communicative function (e.g., when the listener cannot see them). This study explores the intrapersonal function of gestures, and the semantic content of the speech they accompany. Sixty-eight adults participated in pairs, communicating on an object description task. Visibility of partner was manipulated; participants completed half the task behind a screen. Participants produced iconic gestures significantly more for praxic items (i.e., items with physicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
28
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 26 publications
(41 reference statements)
6
28
0
2
Order By: Relevance
“…Participants produce representational gestures at a higher rate when they have physically constructed the patterns than when they have only viewed the patterns. Results from these two studies are consistent with the action generation hypothesis because they show that action generation potential (Pine et al, 2010) or action generation experience (Hostetter & Alibali, 2010) can increase the production of co-speech gestures. However, in Pine et al (2010) and Feyereisen and Havard (1999), the speech contents were different when participants described the manipulable and nonmanipulable items.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…Participants produce representational gestures at a higher rate when they have physically constructed the patterns than when they have only viewed the patterns. Results from these two studies are consistent with the action generation hypothesis because they show that action generation potential (Pine et al, 2010) or action generation experience (Hostetter & Alibali, 2010) can increase the production of co-speech gestures. However, in Pine et al (2010) and Feyereisen and Havard (1999), the speech contents were different when participants described the manipulable and nonmanipulable items.…”
supporting
confidence: 73%
“…Results from these two studies are consistent with the action generation hypothesis because they show that action generation potential (Pine et al, 2010) or action generation experience (Hostetter & Alibali, 2010) can increase the production of co-speech gestures. However, in Pine et al (2010) and Feyereisen and Havard (1999), the speech contents were different when participants described the manipulable and nonmanipulable items. Hostetter and Alibali (2010) did not report whether speech production differed between the action and the viewing conditions.…”
supporting
confidence: 73%
“…However, there are several reasons to doubt the utility of this design for such a broad hypothesis. First, the results of numerous experiments on the effect of mutual visibility on overall gesture rate have been mixed, with half finding that mutual visibility leads to a significantly higher rate (Alibali, Heath, & Myers, 2001;Cohen, 1977;Cohen & Harrison, 1973;Emmorey & Casey, 2001;Krauss, Dushay, Chen, & Rauscher, 1995;Mol, Krahmer, Maes, & Swerts 2009a, 2009b and the other half finding no significant difference in overall rate (Bavelas et al, 1992(Bavelas et al, , 2008(Bavelas et al, , 2014De Ruiter, Bangerter, & Dings, 2012;Holler, Tutton, & Wilkin, 2011;Pine, Burney, & Fletcher, 2010;Rimé, 1982). Two of the latter studies found both results, depending on the kind of gesture studied (Bavelas et al, 1992;De Ruiter et al, 2012).…”
Section: Mutual Visibilitymentioning
confidence: 99%
“…For quite some time, the one question that appeared to preoccupy many researchers in the field of gesture concerned their global function (i.e., inter-or intrapersonal). Nowadays, there is plenty of evidence that co-speech gestures appear to fulfil both speaker-oriented (e.g., Hostetter et al, 2007;Kita and Davies, 2009;Morsella and Krauss, 2004;Pine et al, 2010) and addressee-oriented functions (e.g., Alibali et al, 2001;Bavelas et al, 2008;Holler and Beattie, 2003b;Jacobs and Garnham, 2007).…”
mentioning
confidence: 99%